VEGETABLE CULTIVATION TRAINING IN SUPPORTING ECONOMIC AND FOOD SECURITY IN COVID 19 PANDEMIC ERA - Hayati, Nur; Nurhayati, Tati; Sodikin, Muhammad Ali; Cahyana, Nana; Marlina, Dina; Yulyana, Ade (Indonesian Journal of Devotion and Empowerment, 2020)
This training is a training on the cultivation of vegetable crops for the local community to stabilize the economy of the community during the covid-19 pandemic. The training held in Rt.05, Sindangheula Village, Banjarharjo District, Brebes Regency involved the participation of citizens while prioritizing health protocols. The purpose of this training is to improve economic conditions amid pandemic conditions that slightly disrupt the economic condition of Sindangheula villagers and educate healthy lifestyles by consuming organic vegetables of their own crops. In addition, this training is also one of the working programs of KKN BMC UNNES Year 2020. This research uses a qualitative approach. The focus in this study is how people use vegetable cultivation to anticipate food and economic problems during the Covid-19 pandemic. This research data source is obtained through primary and secondary data sources. Primary data is obtained by the authors through subject and research informants. The immediate benefit of this training activity is in addition to information and skills how to cultivate vegetables in the yard of the house and can ultimately improve economic and health conditions by producing organic vegetables from the yard of their own home. The target audience of this training activity is mothers and teenagers in Rt.05 Sindangheula Village and the trainees are 4 people. The result of this activity is that the training goes well according to the original plan and the trainees are very enthusiastic about this training and they understand how to cultivate good vegetables. Pelatihan ini adalah pelatihan budidaya tanaman sayuran bagi masyarakat setempat guna menstabilkan ekonomi masyarakat selama pandemic covid-19. Pelatihan yang di laksanakan di Rt.05, Desa Sindangheula, Kecamatan Banjarharjo, Kabupaten Brebes ini melibatkan partisipasi warga dengan tetap mengutamakan protokoler kesehatan. Tujuan pelatihan ini adalah untuk meningkatkan kondisi ekonomi di tengah kondisi pandemic yang sedikit banyak mengganggu kondisi ekonomi warga desa Sindangheula dan mengedukasi pola hidup sehat dengan mengkonsumsi sayuran organic hasil panen sendiri. Selain itu pelatihan ini juga merupakan salah satu program kerja KKN BMC UNNES Tahun 2020. Penelitian ini menggunakan pendekatan kualitatif. Fokus dalam penelitian ini adalah bagaimana masyarakat memanfaatkan budidaya sayuran untuk mengantisipasi masalah pangan dan ekonomi di masa pandemic Covid-19. Sumber data penelitian ini diperoleh melalui sumber data primer dan sekunder. Data primer diperoleh penulis melalui subjek dan informan penelitian. Manfaat langsung dari kegiatan pelatihan ini ialah sebagai tambahan informasi dan keterampilan cara membudidayakan sayuran di pekarangan rumah dan pada akhirnya dapat menyejahterakan kondisi ekonomi dan kesehatan dengan menghasilkan sayuran organic dari pekarangan rumah sendiri. Khalayak sasaran dari kegiatan pelatihan ini adalah ibu-ibu dan remaja di Rt.05 Desa Sindangheula dan peserta pelatihan berjumlah 4 orang. Hasil dari kegiatan ini adalah pelatihan berjalan dengan baik sesuai rencana awal dan peserta pelatihan sangat antusias dengan adanya pelatihan ini dan mereka memahami bagaimana cara membudidayakan sayuran yang baik.